The automated lighting programmer's handbook - Schiller, Brad (Routledge/Taylor & Francis Group, 2022)
"The Automated Programmer's Handbook Fourth Edition provides respected and clear coverage of the process of programming automated lighting fixtures from basic principles to advanced production preparations. This guide helps lighting programmers and designers with the creative and operational challenges they face in their rapidly evolving industry. Concepts, procedures, and guidelines to ensure a successful production are covered as well as troubleshooting, much needed information on workflows, technology, work relationships, console networking, digital lighting, and more. Chapters are peppered with advice and war stories from some of the most prominent lighting designers and programmers of today. The fourth edition is the most comprehensive yet: added topics include programming structure, advanced recording/editing, cloning, multi-cell fixtures, safety routines, GDTF, and Pre-Visualization. Deep explorations into the work of programmers from Earlybird and Broadway provide readers with timely real-world scenarios and advice. The information in this book is perfect for anyone interested in programming of automated lighting in any market. From the beginner to the expert, the methodologies within provide simple, yet powerful tools to assist with any production. Lighting designers also will gain important knowledge about the procedures and concepts utilized by lighting programmers"--